Antibody-induced botulinum toxin treatment failure: A review and novel management approach - Yuttana Srinoulprasert (2020)
© 2020 Wiley Periodicals LLC Background: Botulinum neurotoxin A (BoNT/A) has been used for cosmetic indications for many decades. Consumption of BoNT/A usage has been markedly increased for a few years. Even new formulations of BoNT/A to decrease immunogenicity have been released, repeated treatment to maintain efficacy outcome is inevitable and could finally provoke immune response. In the past, prevalence of botulinum treatment failure (BTF) in cosmetic indication was rare leading to less medical concern. Current decade, case reports on BTF, especially antibody-induced botulinum toxin treatment failure (ABTF), have been increasingly revealed and risk factors associated with ABTF have been intensively studied. Aims: In this article, we will review antibody-induced botulinum toxin treatment failure (ABTF), risk-associated ABTF, prevalence and recent case reports of ABTF, and new approach to deal with ABTF. Methods: Literature search was conducted using PubMed. The relevant literatures published between January 2000 and May 2020 concerning BTF and ABTF including investigation for ABTF were included and analyzed. Results: Possible causes of BTF were summarized. ABTF could be a tip of iceberg of BTF, its prevalence, and currently, 10-year case reports of ABTF were published evidence. Risk factors and investigation methods for ABTF were also summarized. Based on previous studies and our experience, novel approach to management of ABTF was described. Conclusion: Effective management of BTF is to explore causes of treatment failure. Antibodies against BoNT/A complex could be one of many possibilities. Laboratory in vitro tests could be alternative tools to decrease adverse effect and rebooting immune responses in BTF patients.